The development of a nonstationary separation and coherent structures in a two-dimensional viscous incompressible flow around a body - Zakharenkov, M.N. (Archives of Mechanics, 1996)
Two-dimensional viscous incompressible flows around a circular cylinder and a 12% Zhukovsky airfoil are considered. Numerous examples of complex separated flows around these bodies with coherent structures and detached separation generation, as well as examples of flow stabilization and separation destruction are obtained. Numerical experiment technology based on parametrization of the far-field boundary conditions and effect of sequential exclusion of the scheme parameters and problem statement disadvantages is proposed.